Mesangial cells regulate the single nephron GFR and preserve the integrity of the glomerular filtration barrier: An intravital multiphoton microscopy study. (11th March 2021) - Ziegler, Vera; Fremter, Katharina; Helmchen, Julia; Witzgall, Ralph; Castrop, Hayo
Abstract: Aim: The intraglomerular mesangial cells are located between the glomerular capillaries. Here we hypothesized that mesangial cells regulate the single nephron glomerular filtration rate (snGFR) and that mesangial cells support the integrity of the glomerular filtration barrier. Methods: We assessed the function of mesangial cells in vivo by multiphoton microscopy. Mesangial cells were depleted in Munich Wistar Froemter rats using the Thy1.1 antibody model. Results: The Thy1.1 antibody caused the cell‐specific loss of 82 ± 3% of mesangial cells. After mesangial cell depletion, the baseline snGFR was reduced to 12.0 ± 1.2 vs 32.4 ± 3.2 nL/min in controls. In control rats, the snGFR decreased after angiotensin II infusion by 61 ± 3% ( P = .004), whereas it remained unchanged in Thy1.1‐treated rats. The changes in the snGFR after angiotensin II infusion in control rats were accompanied by the marked rotation of the capillary loops within Bowman's space. This phenomenon was absent in anti‐Thy1.1‐treated rats. The glomerular sieving coefficient (GSCA ) for albumin, used as a measure of the integrity of the glomerular filtration barrier, was low in control rats (0.00061 ± 0.00004) and increased after angiotensin II infusion (0.00121 ± 0.00015). In Thy1.1‐treated rats, the GSC was elevated (0.0032 ± 0.00059) and did not change in response to angiotensin II. Electron microscopy revealed the increased thickness of the glomerular basement membrane after mesangial cell depletion. Conclusion: Our data suggest that mesangial cells actively contribute to the regulation of the snGFR. Furthermore, mesangial cells are crucially involved in maintaining the integrity of the glomerular filtration barrier, in part by modulating the thickness of the glomerular basement membrane.